Strafrecht gegen Korruption im Sport? Erscheinungsformen des Match Fixing und Legitimation ihrer Kriminalisierung über die §§ 265c, 265d StGB - Sigmund, Julian (Reihe: Studien zum Wirtschaftsstrafrecht - Neue Folge, 2021)
The thesis examines the legitimacy of the criminal offenses introduced in Sec. 265c, 265d of the German Criminal Code (StGB). First, the addressed bribery-related manipulations of sports competitions are systematized phenomenologically and described in terms of extent and causes. The standard of review derived from the doctrine of legal interests and the principle of proportionality then requires an intensive examination of the content of the integrity of sport, which the legislature has declared to be the object of protection, an analysis of the structures of offenses, and an evaluation of the effectiveness of non-criminal law, in particular internal sports prevention and protection measures. As a result it should be noted: Sec. 265c and 265d of the German Criminal Code (StGB) also show questionable features of the expansive criminal legislation that has characterized recent years.